Building community into property - Byrne, Edmund F. (Journal of business ethics, 1988)
American business's fascination with both laborsaving devices and low wage environments is causing not only structural unemployment and dissipation of the nation's industrial base but also the deterioration of abandoned host communities. According to individualist understandings of the right of private property, this deterioration is beyond sanction except insofar as it affects the property rights of others. But corporate stockholders and managers should not be considered the only owners of property the value of which is due in part to the investments of employees and of the host community. The contributions of the latter should therefore be adequately recognized in law. Short-term job protection and long-term planning for leisure are helpful. But still more important is a recognition in public policy of the interests of the community in property owned by corporations. There is ample precedent in our legal traditions for public preemption of private property; but in contrast to much “taking” in the past, this must be exercized in a manner that is truly for the public benefit.